The genome sequence of Tenthredo notha Klug, 1814, a sawfly [version 2; peer review: 2 approved] - Gavin R. Broad; Steven Falk (Wellcome Open Research, 2024)
We present a genome assembly from an individual female Tenthredo notha (Arthropoda; Insecta; Hymenoptera; Tenthredinidae). The genome sequence is 253 megabases in span. Most of the assembly (99.91%) is scaffolded into 20 chromosomal pseudomolecules. The mitochondrial genome was also assembled and is 19.8 kilobases in length. Gene annotation of this assembly on Ensembl has identified 10,235 protein coding genes.